Philosophical and psychological analysis of moral choices in the game This War of Mine - Neumann, Alicja (Hybris, 2019)
The moral choices made both in the context of everyday life and in the reality of war fascinate psychologists and philosophers focused on experimental research on intuition. In particular, in many psychological articles, the decisions made by the subjects in different variations of the trolley problem are analyzed. Most often, complex stories are presented for respondents and they can choose between two or three options to solve the problem, but it is required to indicate the option that respondent would choose if he/she found himself in the described situation. However, technological development allows the use of increasingly emotionally engaging methods of putting subjects in such dilemmas, including computer games such as This War of Mine, by 11 bit studios. In this paper selected moral choices that players in This War of Mine are facing are considered together with the decisions that were most often made in response to them, based on pilot study. The results of these analyses will be combined with data from psychological research on moral intuitions in various dilemma situations. The aim of the proposed considerations will be to answer the question whether the context of everyday life versus the reality of war affects the change of intuition regarding just action. The significance of this kind of research for philosophical inquiry into the ethics of war will also be discussed.